Mechanisms of public administration in post-soviet societies - Vavreniuk, Sergii A.; Nepomnyashchyy, Oleksandr M.; Marusheva, Oleksandra A.; Lahunova, Iryna A.; Shostak, Svitlana M. (Linguistics and Culture Review, 2021)
This article focuses on the problem of public administration in the countries of the former Soviet Union. It reveals the economic development issues of the states of the post-Soviet space, considers the main common and distinctive features for the newly independent states. The central problem raised in the article is the determination of the current state of the modernization process in post-Soviet societies. The author assumes the presence of demodernization and presents an argument in confirming his opinion. In addition, the article reveals the issues of the modern political state of such countries of the former USSR as Russia, Ukraine and Uzbekistan. The author traces the process of demodernization and dependence of political and social development on the governing elitist groups, leading to authoritarianism as opposed to the supposed democracy and modernization.